INNOVATIVE TEACHING LEARNING PROCESS IN ACCORDANCE TO THE CHANGING WORLD - Arjunsinh, Parmar Kalpana; Soni, Niraliben A. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The goal of comparison, a research paper that was functionally identical was utilized in the evaluation. The objective of the evaluation was to investigate academic performance of “secondary school students” depending on their participation in Innovative teaching learning Process. One hundred pupils from high school of Anand District were chosen according to a random selection method. During the process of analyzing the data, the researcher analyzed estimates for the “mean, the standard deviation, and the t-values”. According to the data, it is advised that children who attend public & private rural schools participate in more Innovative teaching learning Process. This is the case despite the fact that these children have poor academic performance. The outcomes of the study indicated that “secondary school students” who attended urban & non-public schools had a lower engagement rate in Innovative teaching learning Process while concurrently demonstrating higher academic achievement. This was the case despite academic accomplishment being higher.